Demographic features and laboratory parameters among hospitalized vaccinated patients with covid-19 in Istanbul, Turkey - KARAHASAN, AYŞEGÜL (My University, 2023)
BackgroundThe number ofCOVID-19cases has been decreasing recently, and the restrictions are waived in many countries. The data aboutvaccineefficacy are essential to be prepared for the future even if the pandemic ends and the disease becomes endemic.AimsThe aim of this study was to define demographic and laboratory data for disease severity among vaccinatedCOVID-19cases who were hospitalized.Study DesignThis is a retrospective cohort study.MethodsSARS-CoV-2 polymerase chain reaction–positive patients who were fully vaccinated (2 doses of vaccines and 3 doses of vaccines) and had been hospitalized at least 15 days after the lastvaccinedose were enrolled in this study. Patients\" data including laboratory parameters were retrieved, and descriptive statistics and comparison of variables were calculated.ResultsBetween September 1, 2021, and February 28, 2022, 685 patients (mean age, 67.84 years; 50.8% female) were hospitalized. Inactivated whole-virion SARS-CoV-2vaccine(CoronaVac) had been administered to 467 of the patients (68.4%), BNT162b2 mRNAvaccine(Pfizer-Pfizer-BioNTech) had been administered to 107 of the patients (15.6%), and to 111 of the patients (16%), a combination of 2 vaccines had been administered. At least 1 comorbidity was present in 160 participants (23%) and more than 4 comorbidities in 46 patients (6.6%). The most common comorbidity was hypertension (349, 50.2%). The presence of comorbidities was significantly higher in patients having 3 doses ofvaccine. Increased ferritin levels were determined in 56.4% of the patients, increased D-dimer levels in 69.9% of the patients, increased C-reactive protein levels in 79.7% of the patients, and increased procalcitonin levels in 61.5% of the patients. A total of 36.4% of the patients had decreased lymphocyte counts, 20% had low lymphocyte/monocyte ratio, and 22% had decreased neutrophil/lymphocyte ratio. The only parameter that was significantly higher in patients having 3vaccinedoses was procalcitonin. Mean duration of hospitalization was 9.68 ± 7.29 days. In the CoronaVac and Pfizer-BioNTech groups, 68.5% and 21.4%, respectively, of the patients were older than 65 years. Seventeen (3.6%) patients in the CoronaVac group, 6 (5.4%) patients in the combination group, and 3 (2.8%) patients in Pfizer-BioNTech group had been admitted to the intensive care unit. Mortality rate was 0.3% (2 of 685 patients).ConclusionsThe incidence of severeCOVID-19disease among fully vaccinated patients is low even in the presence of comorbidities, older age, and presence of abnormal laboratory parameters, regardless of thevaccinetype.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); COVID-19; vaccine; epidemiology